Vídeo informativo sobre a influência da espiritualidade/religiosidade para o bem-estar dos idosos - Albuquerque, Vívian Lacerda Wanderley de (2022)
Introduction: It is known that religion and spirituality have a relevant contribution to the well-being of the individual, being a tool to help face crisis situations. Thus, it is important to study strategies to mitigate the damage caused, especially to the elderly population, by the situation caused by the pandemic of COVID-19. Objectives: To extract from the literature scientific evidence about the influence of spirituality/religiosity on the elderly population in crisis situations. To investigate the influence of spirituality/religiosity on the well-being of the elderly in crisis situations. To make an informative video about the influence of spirituality/religiosity on the well-being of the elderly in times of crisis such as the Covid-19 pandemic. Material and Methods: This is an exploratory study with a qualitative approach. A survey was conducted with elderly people registered at CRAS and CENTROCOR. Data were collected through clinical evaluation and semi-structured interviews, whose answers were recorded for later analysis, in addition to socio-demographic data of the participants (age, education, monthly income, religion). The data were evaluated by content analysis, to apprehend the contribution of religion/spirituality during the COVID-19 pandemic to the well-being of the elderly assessed, previously processed in the IRAMUTEQ software.